Digital Twin and Its Implementation in 3D Printing: A Research Review - Bhattarai, Piyush Mohan; Shrestha, Pragyee; Chohan, Raju (International Journal of Scientific Research and Management (IJSRM), 2022)
The emergence of Additive Manufacturing (AM) has created a plethora of opportunities for different industries due to its application in 3D printing technology. Since its introduction back in 1980, 3D printing technology has overseen numerous developments and changes.  A rarity back in the day, 3D printing has now become cheaper and available for everyone who wishes to learn and experiment with the technology. Although 3D printing technology can produce optimized and detailed printing at a cheaper rate than in earlier days, it can still be time-consuming and quite costly due to the technology's tendency to follow the trial-and-error method when printing. A proposed solution to such an issue is by implementing Digital Twin (DT), a virtual representation of an object that provides real-time reflection between the virtual and physical space and can interact and converge with the flow of data between both spaces. However, despite the need, Digital Twin is yet to achieve its fullest potential due to a gap in knowledge regarding its concept and development methods. This paper, therefore, intends to provide a brief review regarding the implementation, applications as well as challenges of DT for 3D printing, to provide an understanding of the current trends that can be utilized for further research regarding Digital Twin and its implementation in 3D printing.